Problems and objectives of children's health care in Russia - T.V. Yakovleva; A.A. Baranov ("Paediatrician" Publishers LLC, 2011)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (2): 7-11)